Topographic and Biomechanical Changes after Application of Corneal Cross-Linking in Recurrent Keratoconus - Pedrotti, Emilio (Int J Environ Res Public Health, 2019)
Background: Recurrent keratoconus (RKC) develops as a progressive thinning of the peripheral and the inferior cornea after keratoplasty, in both graft and host, causing secondary astigmatism, refractive instability, and reduced visual acuity. We evaluated the effectiveness of corneal cross-linking (CXL) in patients diagnosed with RKC. Methods: Accelerated-CXL via the epi-off technique was performed in15 patients (18 eyes) diagnosed with RKC. Topographic and biomechanical changes were assessed at 12 months. Results: Differences in maximum keratometry, thinnest corneal thickness, and biomechanical parameters (deformation amplituderatio, inverse concave radius, applanation 1 velocity, and applanation 2 velocity, stiffness A1) versus baseline were statistically significant (p < 0.05).Best corrected visual acuity was improved in 13 eyes and unchanged in 4;manifest refractive spherical equivalent was reduced in 13 eyes, increased in 3,and unchanged in 1 eye; topographic astigmatism was reduced in 9 eyes, remained stable in 1 eye, and increased in 7 eyes. Conclusions: Improved topographic and biomechanic indexes at 1 year after CXL suggest it‘s potential as first-line therapy for RKC, as it is for KC.